"WINGS" TECHNOLOGY AS A MEANS OF COUNTERACTION TO VIOLENCE AGAINST WOMEN FROM A HIGH RISK GROUP (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
This topic is actual in the context of high levels of violence against drug addicted women and women in sex industry and insufficient opportunity for them to apply for relevant social services in Ukraine.The article considers the functional components of the complex preventive and rehabilitation technology "Women Initiating New Goals of Safety", developed by a group social intervention of the Columbia University (USA) in order to reduce the risk of violence against women with drug dependence. This technology was adapted and applied for a pilot project to verify its effectiveness in Ukraine.The sample of the study consisted of 20 women with drug addiction who have experience of violence against them. In addition, in order to assess the qualitative component of the WINGS technology, an in-depth interview was conducted by 2 experts (psychologist and social worker) of an independent governmental organization to provide services to HIV-infected people, who had the experience of conducting an intervention using the method "WINGS". Another tool for evaluating the qualitative characteristics of this technology was the sessions of two focus groups of 12 participants who had the experience of passing WINGS as clients. A separate plan for security was developed for women who works in sex industry, taking into account, that the experience shared by participants in the focus groups of them is unique and significantly different from the experience of other women. Conducted focus groups found elements of quality performance, especially in the security planning and prevention of violence among intimate partners.Providers, who give services to the situation of violence, appreciate their experience of using the WINGS methodology as useful and positive.Pilot studies of using the "WINGS" technology in Ukraine showed results, that allow us to make the previous assumptions about its significant efficiency. At the same time, it helped identify the elements that need to be adapted and refined.
Keywords: prevention of violence, women with drug addiction, short-term intervention, gender-based violence, social service.